Converting ash into reusable slag at lower carbon footprint: vitrification of incineration bottom ash in MSW-fueled demonstration-scale slagging gasifier - Heberlein, Stephan (2024)
Globally waste incineration is becoming the predominant treatment method of solid waste. The largest fraction of solid residue of this process is incineration bottom ash (IBA) requiring further treatment before applications such as in the construction industry become feasible. In this study, vitrification of IBA was conducted in a demonstration-scale high-temperature slagging gasification plant fueled with MSW and biomass charcoal as a green auxiliary fuel. High IBA co-feeding rates of up to 491 kg/h (equivalent to 107% of MSW feeding rate) were achieved during the trials. A highly leaching-resistant slag immobilizing heavy metals in the glass-like amorphous structure and recyclable iron-rich metal granules were generated in the process. The heavy metal migration into the solid by-product fractions depended on the IBA feeding rates and process conditions such as cold cap temperature, charcoal-to-ash ratio, and gasifier temperature profile. Slaked lime and activated carbon powder were used in a dry flue gas treatment and stack gas emissions were kept well below Singapore's regulatory limits. Steam from the hot flue gas was generated in a boiler to drive a steam turbine. The application of biomass charcoal instead of fossil fuels or electricity lead to a lower carbon footprint compared to alternative vitrification technologies. The overall results reveal promising application of high temperature slagging gasification process for commercial-scale vitrification of IBA.